KONSTRUKSI MAKNA NARATIF ALKITAB DALAM PRAKTIK PEMBELAJARAN PENDIDIKAN KRISTEN ANAK USIA DINI - Darmiati Sule; Lita; Elvira Valerin Buntu Langi'; Meri Rongi'; Gresia Puspita Tandirau (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
Christian Early Childhood Education places biblical narratives as the primary medium for children's faith formation. Previous studies have extensively discussed storytelling methods, visual media, and multisensory activities, yet none have critically analyzed how the process of narrative meaning construction itself unfolds when teachers adapt biblical texts for young children. This study aims to analyze the process of biblical narrative meaning construction in Christian Early Childhood Education and to analyze the theological and pedagogical consequences of this process for children's faith formation. A qualitative descriptive method was employed through a library research approach and thematic analysis of theological, pedagogical, and Christian education sources. Results indicate that teachers actively reduce, simplify, and shift the theological meaning layers of biblical texts through mechanisms of narrative selection, language and concept adjustment, and moral extraction, with teachers serving as theologically non-neutral mediators of meaning. The consequences include both the risk of losing the kerygmatic dimension of biblical narratives and the opportunity for more relational and incarnational faith formation. This study concludes that responsible narrative meaning construction demands deep hermeneutical awareness from teachers to prevent the core gospel message from being reduced to mere moral lessons in the pedagogical adaptation process.